The Role Of The Internet In Improving The Performance Of Household Assistants At LPK Budi Mulia - Riati, Riati; Mustofa, Riyadi; Mar’aini, Mar’aini; Nefrida, Nefrida (Doctoral Program of Social Science, Pasundan University, 2025)
The Internet is a global network that connects millions of devices around the world, enabling the exchange of information quickly and easily, allowing us to access various kinds of information, including information on various menus for household dishes.Utilizing the internet for communication, whether through audio, visual, or audio-visual (video calls), is now possible, regardless of distance and time. The internet also allows everyone to easily find all the information they need. This is because it can connect devices online to exchange data. The breadth of information the internet can provide makes it accessible to various segments of society, including domestic helpers.The internet has penetrated nearly every aspect of modern life, including the world of work and household services. For domestic helpers, an internet connection offers significant benefits in improving their performance, efficiency, and ability to provide better service. The activity was held at the Budi Mulia LPK. This activity was implemented due to the identified problems among domestic helpers in carrying out their daily work. All participants were female. The activity ran smoothly, with participants understanding the counseling material and being motivated to utilize the internet to improve their performance. Proper and effective internet use can improve the work capabilities of domestic helpers, and it is hoped that this will increase their salaries and improve the family's economic well-being.